Tingkat Percaya Diri Siswa Kelas VII di MTsN 01 Kota Malang dalam Pembelajaran Blended Learning - Destanika Dhiffa Ralianti; Djoko Budi Santoso; Devy Probowati (Universitas Negeri Malang, 2022)
Abstract: Self-confidence is a mindset that feels confident in your abilities. This study aims to describe the level of self-confidence of class VII MTsN 01 Malang City students in blended learning. The research design uses a quantitative approach with a survey. The total population of class VII is 386 students and the number of samples is 270 students. The sampling technique is simple random sampling. Data collection using a questionnaire. Data analysis used descriptive statistical analysis which was presented in percentage form. The results showed that the overall level of self-confidence was in the high (17 percent), medium (83 percent), low (0 percent) category. The level of self-confidence based on gender, namely the female students in the high category (23 percent), medium (77 percent), low (0 percent). Meanwhile, the self-confidence level of male students is in the high category (14 percent), medium (86 percent), low (0 percent). The level of confidence in the aspect of is in the high category (12 percent), medium (87 percent), low (1 percent). On the optimistic aspect in the high category (29 percent), medium (70 percent), low (1 percent). In the objective aspect in the high category (64 percent), medium (36 percent), low (0 percent). In the consequent aspect in the high category (34 percent), medium (66 percent), low (0 percent). And on the rational and realistic aspects in the high category (22 percent), moderate (74 percent), low (4 percent). Based on these data, it is concluded that the level of self-confidence of class VII students in blended learning tends to be medium. Abstrak: Percaya diri ialah suatu pola pikir bahwa merasa yakin akan kemampuan diri. Penelitian bertujuan mendeskripsikan tingkat percaya diri siswa kelas VII MTsN 01 Kota Malang dalam pembelajaran blended learning. Rancangan penelitian menggunakan pendekatan kuantitatif dengan survei. Jumlah populasi dari kelas VII sebanyak 386 siswa dan jumlah sampel sebanyak 270 siswa. Teknik pengambilan sampel ialah simple random sampling. Pengumpulan data menggunakan angket. Analisis data menggunakan analisis statistik deskriptif yang disajikan dalam bentuk persentase. Hasil penelitian menunjukkan tingkat percaya diri secara keseluruhan dalam kategori tinggi (17 persen), sedang (83 persen), rendah (0 persen). Tingkat percaya diri berdasarkan jenis kelamin yaitu pada siswa perempuan dalam kategori tinggi (23 persen), sedang (77 persen), rendah (0 persen). Tingkat percaya diri siswa laki-laki dalam kategori tinggi (14 persen), sedang (86 persen), rendah (0 persen). Tingkat percaya diri pada aspek keyakinan diri dalam kategori tinggi (12 persen), sedang (87 persen), rendah (1 persen). Pada aspek optimis dalam kategori tinggi (29 persen), sedang (70 persen), rendah (1 persen). Pada aspek objektif dalam kategori tinggi (64 persen), sedang (36 persen), rendah (0 persen). Pada aspek konsekuen dalam kategori tinggi (34 persen), sedang (66 persen), rendah (0 persen). Dan pada aspek rasional dan realistis dalam kategori tinggi (22 persen), sedang (74 persen), rendah (4 persen). Berdasarkan data tersebut, disimpulkan bahwa tingkat percaya diri siswa kelas VII dalam pembelajaran blended learning cenderung sedang.